Handbook of Medieval Culture - Classen, Albrecht (De Gruyter, 2015)
A follow-up publication to the Handbook of Medieval Studies, this new reference work turns to a different focus: medieval culture. Medieval research has grown tremendously in depth and breadth over the last decades. Particularly our understanding of medieval culture, of the basic living conditions, and the specific value system prevalent at that time has considerably expanded, to a point where we are in danger of no longer seeing the proverbial forest for the trees. The present, innovative handbook offers compact articles on essential topics, ideals, specific knowledge, and concepts defining the medieval world as comprehensively as possible. The topics covered in this new handbook pertain to issues such as love and marriage, belief in God, hell, and the devil, education, lordship and servitude, Christianity versus Judaism and Islam, health, medicine, the rural world, the rise of the urban class, travel, roads and bridges, entertainment, games, and sport activities, numbers, measuring, the education system, the papacy, saints, the senses, death, and money
10.1515/9783110267303
Keywords: Civilization; Medieval / Handbooks; manuals; etc; Civilization; Medieval; Cultural history; Kulturgeschichte; Medieval Studies; Mediävistik; Middle Ages; Mittelalter; HISTORY / Medieval